Undergraduate research in schools offering library and information science courses in Metro Manila (1992-1997) - Arellano, Christine B. (1998)
This study is undertaken to show the research patterns in the field of library and information science in the undergraduate level. The general objectives of the study are: to know the trends in Library and Information Science (LIS) research in thirteen undergraduate LIS schools in Metro Manila; to draw suggestions for further studies in the area; and to make recommendations on evaluating and developing research in the LIS field. The specific objectives of this study are: to know what topics or areas are usually researched on or evaluated by LIS students of LIS schools in Metro Manila; to find out if there is any shift in terms of research topic or area of study in the field of LIS from 1992 to 1997; to know what method of research is predominantly used; to find out if there is any significant change in the trend of the method employed in conducting the research; to know the possible relationships between the areas of research and the gender of the researchers; and to know the possible relationships between the methodology used and the gender of the researcher.